High Level of Tumor Necrosis Factor (TNF)-Î± is a Risk Factor for Preeclampsia - Anom, I.G.N. (Indonesian Socety of Obstetrics and Gynecology, 2012)
Objective: To define that elevated TNF-Î± serum level was the risk factor of preeclampsia in pregnancy. Method: This research is a case-control study. From 56 pregnant women, there are 28 women with preeclampsia and the other 28 women with normal pregnancy. Then the serum level of TNF-Î± was obtained at Prodiaâs clinical Laboratory Denpasar. Dataâs normality test was done with Kolmogorov-Smirnov, then an analysis of data was done with Independent Sample Test, predictive value a = 0.05. To define the role of TNF-Î± level in preeclampsia, Chi-Square test was chosen. Result: From this research we found the average level of TNF-Î± in preeclampsia (6.64 Â± 7.64 pg/ml) was higher than in normal pregnancy (2.42 Â± 1.77 pg/ml). Analysis with t-independent test shows that the t-value was 2.85 and p-value was 0.006, which means that the average level of TNF-Î± between the two group was significantly different (with predictive value, p